Assessment of paraspinal muscle characteristics, lumbar BMD, and their associations in routine multi-detector CT of patients with and without osteoporotic vertebral fractures. Issue 125 (April 2020) - Sollmann, Nico; Franz, Daniela; Burian, Egon; Löffler, Maximilian T.; Probst, Monika; Gersing, Alexandra; Schwaiger, Benedikt; Pfeiffer, Daniela; Kirschke, Jan S.; Baum, Thomas; Riederer, Isabelle
Highlights: This study investigates paraspinal muscle characteristics, BMD, and their associations. Gender and osteoporotic vertebral fracture status were used for patient categorization. Males showed significantly higher BMD, CSA, and CSA ratios at the levels L2 and L4/5. No differences were observed between patients with or without fractures (except for BMD). Abstract: Purpose: To investigate paraspinal muscle characteristics and lumbar bone mineral density (BMD) and their associations in routine abdominal multi-detector computed tomography (MDCT) as well as the impact of osteoporotic vertebral fractures on such associations. Method: 116 patients (69.7 ± 8.1 years, 72 males) who underwent routine abdominal MDCT (oncological staging and/or follow-up for tumor recurrence) were retrospectively included and assigned to a fracture and control group (age- and gender-matched), depending on the presence or absence of lumbar osteoporotic vertebral fractures. BMD was derived from lumbar vertebrae using a conversion equation, and the cross-sectional area (CSA), CSA ratio (CSA psoas muscles divided by CSA erector spinae muscles), and muscle attenuation were measured for the psoas and erector spinae muscles at the levels L2 and L4/5 without dedicated software. Results: Males showed significantly higher BMD, CSA, and CSA ratios at the levels L2 and L4/5, while females had decreased erector spinae muscle attenuation at L4/5 (p < 0.05). No significant differences between patients with versus without fractures were observed except for BMD (68.5 ± 37.2 mg/ml vs. 91.4 ± 26.8 mg/ml; p < 0.01). Age-adjusted partial correlation testing revealed significant correlations of BMD and the CSA ratio at level L4/5 (r = 0.20; p = 0.03), but not with muscle attenuation (p > 0.05). Conclusions: Paraspinal muscle characteristics and lumbar BMD can be assessed seamlessly in routine abdominal MDCT without dedicated software. There are level-dependent interactions between paraspinal muscle characteristics as well as lumbar BMD. Vertebral fracture status was independent of paraspinal muscle characteristics.